2012
DOI: 10.4186/ej.2012.16.5.177
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Agricultural By-Products for Alpha-Amylase Production under Solid State Fermentation by Bacillus Subtilis

Abstract: The production of alpha-amylase by Bacillus subtilis was investigated under different cultivation conditions on two different solid substrates as the support, i.e. oil palm empty fruit bunch (OPEFB) fibers and rice straw using solid state fermentation (SSF) process. Both solid substrates were first pre-treated using NaOH to remove lignin and silica and to break down the hemicellulose structures. The influences of incubation time, incubation temperature and the additional carbon and nitrogen sources on the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…The model offered a relatively high determination coefficient with an R 2 value of 0.8776 (Table 4), indicating the model could explain 87.6% of the responses variability. Predicted R 2 (0.666) was in reasonable agreement with the adjusted R 2 (0.767) (Table 4) since the difference between both R 2 was < 0.200 (Hassan and Karim, 2015). The degree of accuracy with which the experiments were associated was indicated by the coefficient of variation (CV); a high value of CV usually indicated a lower reliability of the experiment (Prajapati et al, 2014).…”
Section: Response Surface Methodologysupporting
confidence: 52%
See 3 more Smart Citations
“…The model offered a relatively high determination coefficient with an R 2 value of 0.8776 (Table 4), indicating the model could explain 87.6% of the responses variability. Predicted R 2 (0.666) was in reasonable agreement with the adjusted R 2 (0.767) (Table 4) since the difference between both R 2 was < 0.200 (Hassan and Karim, 2015). The degree of accuracy with which the experiments were associated was indicated by the coefficient of variation (CV); a high value of CV usually indicated a lower reliability of the experiment (Prajapati et al, 2014).…”
Section: Response Surface Methodologysupporting
confidence: 52%
“…This study showed a low CV of 21.08% (Table 4), signifying that the experiments performed were dependable. The signal to noise ratio is measured by the adequate precision (Hassan and Karim, 2015). The study showed a ratio of8.684 (Table 4) for adequate signal (a ratio greater than 4 is desirable), implying that the model was reliable in optimizing the chosen process variables for maximum amylase production.…”
Section: Response Surface Methodologymentioning
confidence: 95%
See 2 more Smart Citations
“…In this study 0.6% yeast extract yield maximum titer of amylase in submerged fermentation. Hassan and Karim () suggested that supplementation of 0.01 g/g yeast extract as nitrogen source favored amylase production in solid state fermentation of rice straw by Bacillus subtilis . Higher secretion of starch digesting enzyme has been reported for Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%